The Fetal Origins of the Metabolic Syndrome: Can We Intervene? - Noelle Ma; Daniel B. Hardy (Journal of Pregnancy)
Epidemiological studies have suggested that metabolic programming begins during fetal life and adverse events in utero are a critical factor in the etiology of chronic diseases and overall health. While the underlying molecular mechanisms linking impaired fetal development to these adult diseases are being elucidated, little is known about how we can intervene early in life to diminish the incidence and severity of these long-term diseases. This paper highlights the latest clinical and pharmaceutical studies addressing how dietary intervention in fetal and neonatal life may be able to prevent aspects of the metabolic syndrome associated with IUGR pregnancies.